Held, Birger and Wallensteen, Peter, Peacekeeping operations: global patterns of intervention and success, 1940-2000, Folke Bernadotte Academy Publications, Estocolmo, 2004 - Ruiz, Xira (UNISCI Discussion Papers, 2005)
Sin resumen